Small extracellular vesicles from iPSC-MSC lose their regenerative potential upon UV-C irradiation - Biani, María Celeste (2021)
Mesenchymal Stem Cells derived from induced Pluripotent Stem cells (iPSC-MSC) have become a promising alternative to classical Mesenchymal Stem Cells in regenerative medicine. Their properties -as immunomodulatory and regenerative capacities-are in part due to the secretion of Extracellular Vesicles (EVs). Small EVs (sEVs) with sizes that range from 50 to 120 nm contain proteins, lipids, and nucleic acids that exert a role in cellular communication. Their content will depend on the cell of origin and its physiological state, thus the message they convey might change in response to changes in cellular conditions. In particular, the DNA damage response (DDR) has been reported to modulate sEVs secretion. In this work, we analyze how UV-C radiation upon iPSC-MSC alter sEVs secretion, cargo and bystander effect. Here, we confirm that UV-C radiation causes DDR in a dose dependent manner. In addition, we found that UV-C induced stress did not modulate the expression of genes that participate in sEVs biogenesis pathway. Consequently, we found that the amount of sEVs secreted by radiated and non-irradiated cells remained stable. However, sEVs from radiated cells were unable to promote cell migration in their target cells. Moreover, a label-free proteomic analysis revealed that UV-C induced DDR produces sEVs with an altered cargo, rich in migration-inhibiting proteins, and resulting in a less stromal-oriented repertoire.